2018
DOI: 10.1007/s00431-018-3088-z
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride-glucose index, an insulin resistance marker in newborns?

Abstract: • This is the first study where TyG has been assessed in neonates. • TyG appears to be a suitable and cheap tool for identifying insulin resistance at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Insulin resistance plays a crucial role in the pathogenesis of the metabolic syndrome, a significant cardiovascular disease risk factor, by causing reduced glucose metabolism, impaired insulin action, and changes in hepatic lipid metabolism. The TyG index can be used to inexpensively test insulin resistance in clinical settings [6,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance plays a crucial role in the pathogenesis of the metabolic syndrome, a significant cardiovascular disease risk factor, by causing reduced glucose metabolism, impaired insulin action, and changes in hepatic lipid metabolism. The TyG index can be used to inexpensively test insulin resistance in clinical settings [6,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Although the reasons for no-reflow creation are debatable, a number of studies have linked it to coronary artery spasm, atherosclerotic plaque embolization, and severe abnormalities of glucose metabolism [3][4][5]. Many investigations have shown that the triglyceride/glucose (TyG) index is a new measure of insulin resistance and is also connected with coronary atherosclerosis, glucose and lipid metabolism problems, and microvascular endothelial dysfunction [6][7][8][9][10]. The establishment of the "no-reflow" syndrome after PCI is also facilitated by these pathologic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…У взрослых верхняя граница по данным зарубежной литературы составляет 8,8 [14]. По данным испанского исследования Gesteiro E., et al (2018), верхняя граница у новорожденных составляет 7,8 [15], а по результатам крупного иранского исследования точка отсечения у детей в возрасте от 7-18 лет -8,33 [16]. По нашим данным, индекс не выходил за рамки ориентировочно нормальных, но, тем не менее, необходимы крупномасштабные исследования на детской популяции с целью определения нормальных значений индекса в соответствии с возрастными периодами.…”
Section: обсуждение основного результата исследованияunclassified
“…Some studies have shown that it is associated with coronary artery spasm and contraction [4], atherosclerotic plaque embolization [5], and severe glucose metabolism disorders [6]. TyG index has been proved to be a novel marker of insulin resistance [7], and is also associated with coronary atherosclerosis [8], glucose and lipid metabolism disorders [9][10], and microvascular endothelial dysfunction [11]. The above factors are also important pathological mechanisms for the occurrence of "no re ow "phenomenon after PCI.…”
Section: Introductionmentioning
confidence: 99%